Labor Supply in the Presence of Taxes: An Alternative Specification - Yatchew, Adonis J. (The Review of Economics and Statistics, 1985)
This paper estimates a model of married women's labor supply in the presence of progressive taxes. The specification is based on a translog indirect utility function with normally distributed random preference parameters. The application of Roy's Identity then leads to a distribution of labor supply that involves ratios of normals.